Sclerosing variant of mucoepidermoid carcinoma: a diagnostic challenge - Rasul, Usman (BMJ Case Rep, 2020)
The sclerosing variant of mucoepidermoid salivary gland carcinoma is extremely rare. It is nearly impossible to diagnose this condition preoperatively. We present a case of a 23-year-old woman with a 1-year history of left parotid enlargement with inconclusive fine-needle aspiration cytology results. MRI showed an irregular parotid mass, and subsequent partial parotidectomy confirmed the diagnosis. We discuss the diagnostic pitfalls of this condition and provide a review of the literature surrounding its pathogenesis and management.